2010
DOI: 10.1111/j.1754-9485.2010.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of methods of analysis in contouring studies for radiation oncology

Abstract: Inter-observer variability in anatomical contouring is the biggest contributor to uncertainty in radiation treatment planning. Contouring studies are frequently performed to investigate the differences between multiple contours on common datasets. There is, however, no widely accepted method for contour comparisons. The purpose of this study is to review the literature on contouring studies in the context of radiation oncology, with particular consideration of the contouring comparison methods they employ. A l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 87 publications
0
108
0
Order By: Relevance
“…The JI [18][19][20], DICE [4], Hausdorff distance [21] and Kappa (κ) statistic [22,23] outlined in Supplementary Table 1, are metrics commonly used to establish inter-observer variation [6]. JI and DICE values from CERR were verified in 3D Slicer [24][25][26] and MILXview and were consistent to within 2 significant figures.…”
Section: Analysis Metricsmentioning
confidence: 75%
“…The JI [18][19][20], DICE [4], Hausdorff distance [21] and Kappa (κ) statistic [22,23] outlined in Supplementary Table 1, are metrics commonly used to establish inter-observer variation [6]. JI and DICE values from CERR were verified in 3D Slicer [24][25][26] and MILXview and were consistent to within 2 significant figures.…”
Section: Analysis Metricsmentioning
confidence: 75%
“…[11][12][13] As recommended by these reviews, we used three different types of metrics to evaluate the outlining agreement achieved. The simplest was using a comparison of volume [in terms of percentage volume difference (PVD)].…”
Section: Outlining Studiesmentioning
confidence: 99%
“…The DSC metric is commonly used in studies of contouring variability [10]. In this study, DSC demonstrated the highest compliance value for bladder (0.971), followed by prostate (0.838), and then rectum ( 0.771) There are several possible reasons for the high similarity among bladder contours compared to other contours.…”
Section: Discussionmentioning
confidence: 75%